Accurate detection of α-globin gene copy number variants with two reactions using droplet digital PCR - Bao, Xiuqin; Qin, Danqing; Ma, Jian; Zhou, Xiangcheng; Wang, Jicheng; Yao, Cuize; Zhang, Liang; Du, Li (Hematology (Luxembourg), 2022)
The α-thalassemia is a highly prevalent disease in tropical and subtropical regions, including southern China, and is mainly caused by deletion in α-globin genes (HBA1 and HBA2). The clinical manifestation of α-thalassemia is highly correlated with the copy number of α-globin genes. The decrease in copy number results in α-thalassemia, while duplication or triplication compounded with β-thalassemia may aggravate the clinical manifestation. However, the common methods used to measure the copy number variants can only detect the three common types: - SEA , -α 3.7 , and -α 4.2 , and may easily miss the rare deletional type and duplication or triplication cases. Therefore, a new method that allows the detection of different copy number variants in α-globin genes simultaneously and accurately needs to be established. A total of 428 peripheral-blood and fetal chorionic villus or amniotic fluid samples were used in this study. We employed a pair of primers and two probes, one for HBA1 and another for HBA2, to perform droplet digital polymerase chain reaction (ddPCR). Each reaction needed the ddPCR of RPP30 as a reference gene to calculate the copy number. We accurately detected the copy number variants in α-globin genes, including the common form α-thalassemia, triplications such as ααα anti4.2 , and trisomy 16, by performing only two reactions. The accuracy rate for detecting the copy number of α-globin genes was up to 100%. In conclusion, ddPCR served as an accurate and rapid method for detecting copy number variations in the clinical screening for α-thalassemia.